The chronology of Jäkärlä Ware – Bayesian interpretation of the old and new radiocarbon dates from Early and Middle Neolithic southwest Finland - Markku Oinonen; Petro Pesonen (University of Ljubljana, 2022)
The chronology of the eastern Fennoscandian Neolithic is organized with the help of pottery styles, one of which is southwestern Finnish Jäkärlä Ware. In this paper a number of new radiocarbon dates connected with Jäkärlä Ware and other relevant ceramic groups are presented and discussed. The radiocarbon dates of each group are modelled within a Bayesian chronological framework. Also, the potential reservoir effect in charred crust dates is estimated for each date based on stable carbon isotopic ratios of the crust samples and incorporated into models. Jäkärlä Ware appears to be a short-living and quite a isolated group, which had no chronological contacts with Sperrings 1–2 Wares, but with possible coexistence with Middle Neolithic Typical Comb Ware. Jäkärlä Ware is partly simultaneous with eastern Finnish asbestos-tempered Kaunissaari Ware, and forms with it a short chronological horizon in the turn of the Early and Middle Neolithic of eastern Fennoscandia.